Sosialisasi Gerakan Gemar Menabung (Gemabung) dengan Membuat Celengan dari Bahan Bekas - Oktaviani, Siska; Khairunnisa, Ratna; Adianto, Samsul (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
Good money management can be done by setting aside money for a certain period of time which can later be used when there is a need or what we are often familiar with is saving. Knowledge of finance is not only for adults or parents, early childhood who are still in their golden age also need to be given knowledge and understanding of good saving habits. The purpose of this activity is to provide knowledge and understanding to early childhood in RT. 23 Kelurahan Air Hitam regarding financial management by saving from an early age and helping develop children's creativity to recycle used goods into more useful items in the form of piggy banks. The method used in this activity is the delivery of material on saving activities, demonstrations of making piggy banks, questions and answers, quizzes and evaluation of activities. The socialization of the movement to like to save (gemabung) by making piggy banks from used plastic bottles of mineral water with the children of RT 23 Kelurahan Air Hitam went smoothly and made the children understand the good benefits of setting aside their allowance for savings. Children can also develop their creativity by making piggy banks from used plastic bottles of mineral water